Can Rosuvastatin Reduce the Risk of Thrombosis in Patients with Hypercholesterolemia with its Effect on Coagulation Factors and Homocysteine Levels? - Behnam, Mostafa; Deyhim, Mohammad Reza; Yaghmaei, Parichehreh (Cardiovascular & Hematological Agents in Medicinal Chemistry, 2024)
Background and Objectives Hypercholesterolemia is one of the main risk factors for vascular thrombosis in individuals. Therefore, the use of statins is very effective in reducing cholesterol and can reduce the risk of thrombosis in these patients. Rosuvastatin, a member of the statin family which, inhibits cholesterol synthesis. Very few studies have been done in relation to how rosuvastatin can affect thrombosis. So, this research has been tried whether rosuvastatin can have an effect on coagulation factors and homocysteine as risk factors for thrombosis in hypercholesterolemia? Methods In this experimental study, 60 patients (30 men and 30 women with a mean age of 40-70 years) diagnosed with hypercholesterolemia (cholesterol > 250 mg/dl) participated in this research. 30 patients were prescribed rosuvastatin (20 mg/day), and 30 patients were simultaneously taken placebo for three months. All parameters, including FVIII, FV, Fibrinogen, D-Dimer, plasma homocysteine level and lipid profile, were measured before and after treatment. All the results were statistically compared between the two groups. Results In patients who took rosuvastatin, the drug was able to significantly reduce the concentrations of total cholesterol, triglycerides, and low-density lipoprotein (LDL) (P < 0.001). Also, rosuvastatin was able to reduce the concentrations of homocysteine significantly, D-Dimer (P < 0.001), coagulation factor VIII and factor V (P < 0.05). In patients with hypercholesterolemia who took the placebo, did not affect the mentioned variables (P > 0.05). Conclusion According to the results, it seems that rosuvastatin may be able to reduce the risk of thrombosis in patients by affecting coagulation factors and homocysteine levels.
Keywords: Hypercholesterolemia